Micronutrients in Sepsis and COVID-19: A Narrative Review on What We Have Learned and What We Want to Know in Future Trials - Matteo Rossetti; Gennaro Martucci; Christina Starchl; Karin Amrein (Medicina, 2021)
Sepsis remains the leading cause of mortality in hospitalized patients, contributing to 1 in every 2–3 deaths. From a pathophysiological view, in the recent definition, sepsis has been defined as the result of a complex interaction between host response and the infecting organism, resulting in life-threatening organ dysfunction, depending on microcirculatory derangement, cellular hypoxia/dysoxia driven by hypotension and, potentially, death. The high energy expenditure driven by a high metabolic state induced by the host response may rapidly lead to micronutrient depletion. This deficiency can result in alterations in normal energy homeostasis, free radical damage, and immune system derangement. In critically ill patients, micronutrients are still relegated to an ancillary role in the whole treatment, and always put in a second-line place or, frequently, neglected. Only some micronutrients have attracted the attention of a wider audience, and some trials, even large ones, have tested their use, with controversial results. The present review will address this topic, including the recent advancement in the study of vitamin D and protocols based on vitamin C and other micronutrients, to explore an update in the setting of sepsis, gain some new insights applicable to COVID-19 patients, and to contribute to a pathophysiological definition of the potential role of micronutrients that will be helpful in future dedicated trials.